S29 Cough frequency and morbidity in inpatients with acute respiratory disease. (14th November 2013) - Turner, RD; Birring, SS; Matos, S; Bothamley, GH
Abstract : Introduction: Cough is the unique respiratory symptom. Although associated with a range of conditions it has been little studied in acute respiratory disease. We describe cough frequency and cough-related quality of life in this group. Method: Participants had a diagnosis of acute exacerbation of asthma (asthma), chronic obstructive pulmonary disease (AECOPD), or lower respiratory tract infection (including community-acquired pneumonia) in the absence of the other respiratory disease (LRTI). Quality of life was measured with the Leicester Cough Questionnaire (LCQ-acute), cough severity with a visual analogue scale (VAS) and 24-hour cough frequency with the Leicester Cough Monitor. Results: 40 patients were recruited within a median (interquartile range) of 1 (1–2.3) day ( ) of hospital admission. Median (IQR) age was 57 (41–71) and 63% were female. Geometric mean ± log10 SD cough frequencywas high: 19.7 ± 1.36, 33.8 ± 2.02 and 23.6 ± 1.31 coughs/h for asthma (n = 11), AECOPD (n = 15) and LRTI (n = 14) respectively (Figure); median (IQR) cough bouts/24h: 81 (54–210), 148 (97–197) and 129 (67–197). There was no significant difference between disease groups in these values (p > 0.05 for all two-way comparisons). Diurnal variation and median numbers of coughs/ bout were similar between groups. The 48% of patients who were current smokers coughed more than non-smokers (33.6 ± 1.91 vs 20.2 ± 1.38 coughs/h, p = 0.07). No difference in cough frequency was detected amongst the 25% taking angiotensin converting enzyme inhibitors. Gender had no significant overall effect. Median (IQR) VAS scores were 39 (32–86), 73 (53–100) and 82 (48–91) for asthma, AECOPD and LRTI respectively with no significant difference between them. Cough severity showed a significant correlation with 24-hour cough frequency overall (Spearman' coefficient 0.33, p = 0.05). LCQ-acute scores were lower for LRTI (8.4; 6.4–9.5) than asthma (14.7; 10.7–17.5); p = 0.01 (Figure 1 ). Neither was significantly different from those for AECOPD (11.5; 8.5–15.6). Quality of life did not correlate with cough frequency (Spearman' coefficient -0.13; p = 0.48). Conclusion: Cough frequency in acute respiratory disease is high but with high variation. Cough frequency accounts for only part of morbidity in these conditions.